TERT promoter mutation analysis as a surrogate to morphology and immunohistochemistry in problematic spindle cell lesions of the urinary bladder. Issue 6 (22nd September 2020) - Bertz, Simone; Stöhr, Robert; Gaisa, Nadine T; Wullich, Bernd; Hartmann, Arndt; Agaimy, Abbas
Abstract : Aims: Pseudosarcomatous myofibroblastic proliferations (PSMPs) of the urinary bladder are diagnostically challenging. Diagnostic difficulties are mainly due to frequent cytokeratin expression, variable ALK expression and worrisome morphological features suggestive of malignancy. Conversely, sarcomatoid urothelial carcinoma (UC) may show bland inflammatory myofibroblastic tumour (IMT)‐like morphology. TERT promoter mutations are characteristic events in urothelial cancers, but have not been studied in PSMPs. Methods and results: We compared histomorphological and immunohistochemical features and TERT promoter status in 16 PSMPs and 18 sarcomatoid UC. In a subset of PSMPs, RNA sequencing was performed. At least focal IMT‐like morphology was seen in nine of 17 sarcomatoid UC. Atypical mitoses, differentiated urothelial component and heterologous elements were the most reliable distinguishing histomorphological features of sarcomatoid UC, if present. A panel of immunohistochemistry (IHC) including ALK (clone D5F3), p53 pattern, p63 and GATA3 reliably distinguished PSMP from sarcomatoid UC. GATA3 ( P = 0.001) and p53 patterns (mutant versus wild‐type; P < 0.001) were differentially expressed between PSMPs and sarcomatoid UC. Diffuse pancytokeratin staining was significantly associated with PSMPs (10 of 13) compared to four of 14 sarcomatoid UCs ( P = 0.012). TERT promoter mutations were found in 17 of 18 sarcomatoid UC versus none of 16 PSMPs ( P < 0.001). RNA sequencing revealed ALK genetic rearrangements in one of two ALK‐positive and one of 10 ALK‐negative PSMPs, which revealed a novel FN1/RET gene fusion. Conclusion: Careful histomorphological analysis and differential IHC reliably distinguish the majority of PSMPs and sarcomatoid UC. In equivocal cases, TERT promoter mutation analysis and/or detection of ALK expression/rearrangements are valuable additional diagnostic adjuncts, strongly supporting sarcomatoid UC and PSMP, respectively.